Pemberdayaan Masyarakat Desa Slateng Kecamatan Ledokombo Jember Mengolah Limbah Serbuk Gergaji Sengon Menjadi Biochar - Vega Kartika Sari; Basuki Basuki; Marga Mandala; Nurul Dwi Novikarumsari; Iqbal Erdiansyah (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
The use of high inorganic fertilizers in conventional agriculture can affect soil fertility. Efforts to improve land fertility in order to increase land productivity and at the same time increase farmers' income require integrated and sustainable agricultural business development technology. Biochar applied to paddy fields is able to increase organic carbon which can provide nutrients for organisms in the soil that will provide nutrients for plants. Sengon waste in Slateng Village is abundant and has not been utilized, while most of the livelihoods of the Slateng Village residents are farmers. This activity aims to provide training to members of the Harapan Farmers Group and the local Mosque Youth to be able to process sengon waste into biochar. This activity is carried out in several stages, namely socialization and practice. The result of this activity is that participants gain knowledge about processing sengon waste and produce biochar fertilizer that is ready to be applied.